2011
DOI: 10.1186/1743-7075-8-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma incorporation, apparent retroconversion and β-oxidation of 13C-docosahexaenoic acid in the elderly

Abstract: BackgroundHigher fish or higher docosahexaenoic acid (DHA) intake normally correlates positively with higher plasma DHA level, but recent evidence suggests that the positive relationship between intake and plasma levels of DHA is less clear in the elderly.MethodsWe compared the metabolism of 13C-DHA in six healthy elderly (mean - 77 y old) and six young adults (mean - 27 y old). All participants were given a single oral dose of 50 mg of uniformly labelled 13C-DHA. Tracer incorporation into fatty acids of plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
91
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 37 publications
5
91
1
Order By: Relevance
“…6a, b). The results are consistent with a human study that showed that orally administered 13 C-DHA was retained longer in plasma esterified and unesterified fatty acid pools of elderly than young subjects (Plourde et al 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…6a, b). The results are consistent with a human study that showed that orally administered 13 C-DHA was retained longer in plasma esterified and unesterified fatty acid pools of elderly than young subjects (Plourde et al 2011).…”
Section: Discussionsupporting
confidence: 91%
“…The resulting unesterified DHA can enter the brain to replace DHA lost due to metabolism (DeMar et al 2004). In one human study, incorporation of orally-administered 13 C-DHA into plasma esterified and unesterified fatty acid pools increased with age (Plourde et al 2011), suggesting age-related changes in whole-body including liver DHA metabolism and changes in the liver's capacity to maintain plasma esterified and unesterified DHA concentrations.…”
mentioning
confidence: 99%
“…Short-term administration of an EPA+DHA supplement is accompanied by a higher increase in plasma DHA in healthy older adults than in younger adults ( 18 ). The elderly also metabolize an oral dose of carbon-13-labeled DHA differently than young adults ( 19 ). In neither of these studies were participants separated according to APOE4 genotype.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, older individuals have higher plasma EPA and DHA concentrations in response to supplementation with long-chain n-3 PUFAs than younger adults ( 18 ) or after an oral dose of carbon-13 DHA ( 19 ), suggesting signifi cant differences in n-3 PUFA metabolism in older age.…”
mentioning
confidence: 99%
“…More recently it has been suggested that dietary consumption of seafood as a source of DHA may be more important for prevention of AD than supplementation, with APOEε4 carriers who consumed seafood at least once per week showing a lower burden of neuritic plaques and neurofibrillary tangles at death (Morris et al 2016). However, the discrepancies between intervention studies could also be the product of an alteration to DHA metabolism even in normal, healthy adults with advanced age (Astarita et al 2010;Plourde et al 2011). Needless to say, much work remains to be done in this area to determine the best way of maintaining DHA levels within the brain over the lifespan.…”
Section: Discussionmentioning
confidence: 90%